Spinal Cord Presentation of Biopsy-Proven PET-Positive Giant Cell Arteritis. (7th June 2022) - Swart, Grace; Balgobind, Sapna; Chan, Charles; Fulham, Michael; Riminton, Sean; Mitchell, Emma; Reddel, Stephen William
Abstract : A 63-year-old man presented with sudden bilateral lower limb weakness and right-sided sensory loss to pain and temperature on a background of recently diagnosed biopsy-negative giant cell arteritis (GCA) treated with prednisone 50 mg. Erythrocyte sedimentation rate was normal. Somatosensory evoked potentials revealed central conduction delay. PET/CT imaging revealed major vessel hypermetabolism (Figure 1), indicative of active GCA, confirmed on repeat temporal artery biopsy (Figure 2). Spinal cord involvement was suspected; IV steroids and cyclophosphamide followed by tocilizumab were commenced with good response. Clinicians should be aware of rare manifestations of GCA 1 and PET-CT might be helpful in evaluation of disease activity. 2